Analytical Look at the Recent Past - Ivanova, Maya (Poznańskie Studia Slawistyczne, 2021)
The subject of the article is the review of the book Jubilee and modern. The Cyrillo-Methodian narrative during socialism in Bulgaria by the Polish-Bulgarian scholar Ewelina Drzewiecka (2020). Her monograph is an analysis of the jubilee editions dedicated to the holy brothers Cyril and Methodius and their disciples which were published in socialist Bulgaria. The author’s aim is to trace “the Cyrillo-Methodian story” and turn it into a key for understanding the Bulgarian collective memory for the period between 1944 and the1980s. E. Drzewiecka uses Mary Douglas’ theoretical formulations of the history of ideas and the anthropology of institutions as well as Jan and Aleida Assmann’s concept of cultural memory.